Van der Waals Epitaxial Growth of 2D Metallic Vanadium Diselenide Single Crystals and their Extra‐High Electrical Conductivity. Issue 37 (14th August 2017) - Zhang, Zhepeng; Niu, Jingjing; Yang, Pengfei; Gong, Yue; Ji, Qingqing; Shi, Jianping; Fang, Qiyi; Jiang, Shaolong; Li, He; Zhou, Xiebo; Gu, Lin; Wu, Xiaosong; et al.
Abstract : 2D metallic transition‐metal dichalcogenides (MTMDs) have recently emerged as a new class of materials for the engineering of novel electronic phases, 2D superconductors, magnets, as well as novel electronic applications. However, the mechanical exfoliation route is predominantly used to obtain such metallic 2D flakes, but the batch production remains challenging. Herein, the van der Waals epitaxial growth of monocrystalline, 1T‐phase, few‐layer metallic VSe2 nanosheets on an atomically flat mica substrate via a "one‐step" chemical vapor deposition method is reported. The thickness of the VSe2 nanosheets is precisely tuned from several nanometers to several tenths of nanometers. More significantly, the 2D VSe2 single crystals are found to present an excellent metallic feature, as evidenced by the extra‐high electrical conductivity of up to 10 6 S m −1, 1–4 orders of magnitude higher than that of various conductive 2D materials. The thickness‐dependent charge‐density‐wave phase transitions are also examined through low‐temperature transport measurements, which reveal that the synthesized 2D metallic 1T‐VSe2 nanosheets should serve as good research platforms for the detecting novel many‐body states. These results open a new path for the synthesis and property investigations of nanoscale‐thickness 2D MTMDs crystals. Abstract : 2D metallic 1T‐VSe2 single crystals are synthesized on a mica substrate by a van der Waals epitaxial strategy via a chemical vapor deposition method. The synthesized few‐layer 1T‐VSe2 nanosheets present extremely high electrical conductivity and excellent stability. The charge‐density‐wave phase transition is also detected, showing a similar feature to that of exfoliated VSe2 nanosheets.